Original paperDay to day treatment variations of accelerated partial breast brachytherapy using a multi-lumen balloon - Kuo, Hsiang-Chi; Mehta, Keyur J.; Hong, Linda; Yaparpalvi, Ravindra; Montgomery, Leslie L.; Bodner, William; Tomé, Wolfgang A.; Kalnicki, Shalom (Journal of Contemporary Brachytherapy, 2014)
Purpose : To evaluate the variations of multi-lumen balloon (MLB)-based brachytherapy from simulation day to treatment day and their dosimetric impacts during accelerated partial breast irradiation (APBI). Material and methods: A total of 42 CT images scanned from seven patients were evaluated with regards to daily variation due to of: 1) internal uncertainty: size and shape of balloon, seroma volume; 2) geometrical uncertainty-random: length of each catheter was measured for each fraction (total 70); 3) geometrical uncertainty-systematic: virtual systematic errors were tested by offsetting dwell positions. The original plans (as group A) had a mean value of 96.8% on v 95 of the PTV_Eval. Plans were rerun (as group B) such that the mean value of the v 95 was relaxed to 90.4%. By applying the reference plan to each daily CT image, variations of target coverage under different sources of error were evaluated. Results: Shape and size of the balloon had means of < 1 mm decreased in diameter and < 0.4 cm 3 decreased in volume; the mean seroma volume increased by 0.2 cm 3 . This internal variation has a mean of < 1% difference for both V 90 and v 95 . The geometrical uncertainty made a mean deviation of 2.7 mm per root of sum of square. It caused the degradations of V 90 and v 95 by mean values of 1.0% and 1.2%, respectively. A systematic error of 3 mm and 4 mm would degrade both of V 90 and v 95 by 4% and 6%, respectively. The degradations on target coverage of the plans in group A were statistically the same as those in group B. Conclusions : Overall, APBI treatments with MLB based brachytherapy are precise from day to day. However, minor variation due to daily treatment uncertainties can still degrade tumor bed coverage to an unacceptable coverage when v 95 of the original plan is close to 90%.